Identification of Essential Oils From The Bark of Balik Angin (Alphitonia Incana (Roxb.) Teijsm. & Binn. Ex Kurz) - Tika Nurjanah; Hafiz Ramadhan; Nella Faradillah; Putri Indah Sayakti; Dyera Forestryana; Nafila Nafila (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
One of the components that make up essential oils is phenolic compounds which are widely containedin the leaves and bark of the Balik Angin plant (Alphitonia incana (Roxb.) Teijsm. & Binn. ex Kurz).This study aimed to identify phenolic compounds and antioxidant activity of essential oils from thebark of the Balik Angin plant. The essential oils isolation using hydrodistillation and the compoundswere analyzed using gas chromatography-mass spectroscopy (GC-MS). Qualitatively antioxidantactivity test used thin layer chromatography (TLC) and quantitatively by measuring the absorbance of2,2-diphenyl-1-picrylhydrazyl (DPPH) radicals residue that did not react against compounds reducer.The results showed the essential oils contain major compounds which are methyl salicylate followedby methyl palmitate, 2,2-Dimethyl-1,3-dioxane-4,6-dione, and methyl 12-acetoxyoleate. Qualitativetest results of antioxidant activity with TLC there were four yellow spots on a purple background. Thescavenging activity showed the essential oils had an IC50 of 229.056 ppm, while the gallic acid as acomparative standard obtained an IC50 of 0.618 ppm. The conclusion is the essential oils of BalikAngin bark that produces very weak antioxidant activity.